2021
DOI: 10.1021/acs.jpclett.1c02109
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Two-Dimensional Binary Polymers from Heterotriangulenes for Photocatalytic Water Splitting

Abstract: On the basis of first-principles calculations, we report the design of three twodimensional (2D) binary honeycomb-kagome polymers composed of B-and N-centered heterotriangulenes with a periodically alternate arrangement as in hexagonal boron nitride. The 2D binary polymers with donor−acceptor characteristics are semiconductors with a direct band gap of 1.98−2.28 eV. The enhanced in-plane electron conjugation contributes to high charge carrier mobilities for both electrons and holes, about 6.70 and 0.24 × 10 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 62 publications
0
25
0
Order By: Relevance
“…Following the previous reports, 46–48 we finally calculate the Gibbs free energy profiles of the OER and HER involved in photocatalytic water splitting on the GaSe and β-SnS surfaces, respectively. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the previous reports, 46–48 we finally calculate the Gibbs free energy profiles of the OER and HER involved in photocatalytic water splitting on the GaSe and β-SnS surfaces, respectively. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To address the photocatalytic water splitting, the Gibbs free energy profiles of the OER and HER processes on the GaSe and β-SnS surfaces, respectively, are calculated by adopting the method from previous reports, 46–48 see the ESI †…”
Section: Computational Model and Methodsmentioning
confidence: 99%
“…Recently, low-cost and noble metal-free HER and OER catalysts for overall water splitting have drawn more and more attention. [66][67][68] Considerable time and effort has been devoted to searching for abundant and high-efficiency electrocatalysts with low overpotential. Carbon-based materials have natural advantages from their structural diversity and are costeffective compared with metal-based materials.…”
Section: Application To Water Splittingmentioning
confidence: 99%
“… 25 , 26 The unique attributes of COFs including high crystallinity, a tunable pore size, a large specific surface area, and high chemical and thermal stability make them promising candidates for photocatalysis. 27 32 Very recently, layer-stacked COFs with impressive hydrogen evolution activities have been reported, such as azine-linked N 3 -COF and cyano-vinylene-linked sp 2 c-COF, and it was shown that functionalization of sp 2 c-COF with electron-withdrawing end groups further increased the hydrogen production rate. 18 , 22 Despite the rapid experimental progress, 33 40 few studies reported an STH energy conversion efficiency of above 1%.…”
Section: Introductionmentioning
confidence: 99%